UNRAVELLING THE MOTIVATIONAL FORCES BEHIND PURSUING A POSTGRADUATE DEGREE IN ENGLISH EDUCATION - Iwony Dwi Kristiana; Paulus Kuswandono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This study investigated the motivations of fresh graduate student pursue their postgraduate study in the English Education Master Program at Sanata Dharma University. The objectives of the study are the to examine the psychological needs, intrinsic factors, and extrinsic factors to develop their study. The main research instruments in this study are semi-structured interviews, which are conducted using a qualitative methodology. The findings revealed that the psychological needs related to the reason for pursuing postgraduate study, participants expressed a desire for control over their educational choices and the importance of feeling competent in their field. The study also finds out intrinsic and extrinsic factors, such as skill development, enhanced career prospects, and meeting personal needs, students are encouraged to pursue a graduate degree. The results show that intrinsic motivation, environmental factors, and professional orientation play an important role in students' decisions to pursue a postgraduate education. Although this study provides valuable insights, there are limitations in generalizing the findings to just the population studied. Suggestion for further research involving broader samples and more in-depth analysis is needed to understand the impact of motivation on graduate students' academic and career performance.